The Absence Of The Wellington Dutch Reformed Mission Church On Erf 794: A Symbol Of Tangible And Intangible Heritage, Destroyed And Found - Gerber, Pierre-Jeanne (School of Architecture, Planning and Geomatics, 2024)
This dissertation investigates whether the absence of the Wellington Dutch Reformed Mission Church (DRMC) on Erf 794 in Wellington is a heritage-lacuna. It answers the question by setting out, firstly, how the tangible heritage of the DRMC was embodied in the physical church-building (the process of building and the resulting structure); and secondly, how the DRMC church-building was lost by demolition, including the events that led to the demolition and, specifically, the role that racial discrimination played in this process. Finally, the dissertation sets out how these aspects created intangible heritage and confirms how the intangible heritage is held and preserved in the community today. The dissertation examines the history and context of the DRMC, and why it was formed separately from the Dutch Reformed Church (DRC), which plays a significant role in the tangible and intangible heritage of Wellington DRMC. This is explored to contextualise why the tangible heritage of the demolished DRMC building is so significant compared to the objectively more impressive DRC building which still stands. The study confirms that the DRMC of South Africa, as a racially segregated church denomination, was officially founded on 5 October 1881 by the DRC of South Africa. This historic event happened in a church which had been built in 1845 on the corner of Church and Main Street in the well-preserved 19th -century town of Wellington in the Boland region of the Western Cape province. This church with its Coloured congregation became the first DRMC in South Africa. The impressive DRC building (built by its white congregation in 1840) is located directly opposite the site in question. In 1941 the church building of the DRMC was purchased by the DRC. A condition of the sale was that the DRMC had to demolish the church and clean the plot. As stipulated, the DRMC congregation demolished its church after building a new church building, also as stipulated, at least 500 yards away from the white DRC and not on Church Street. What made this event especially significant was that it occurred nine years before the enactment of the Group Areas Act of 1950 (although there were many removals and attempted urban segregation before the act was implemented). Uniquely, in this case, it was the DRC which stipulated and enforced the physical segregation and demolition and not, as in most other cases, the state. This event had been preceded by 13 years of negotiations between these two churches, which further polarised the community.